Market Power in Competition Cases. - Vickers, J (2006)
The assessment of market power in competition cases is and will remain a cornerstone of competition law and policy. The current review of Article 82 policy is an important opportunity to modernise EC policy towards dominance as well as abuse. This paper, which considers debates about market power in the US twenty-five years ago and in Europe now, argues for a disciplined economic approach to the assessment of dominance that does not unduly emphasise market share thresholds. Discipline is needed to ensure that questions of abuse are pursued only when there really is substantial market power, and analysis of abuse should then be integrated with analysis of dominance. Market shares are but one part of the proper assessment of dominance, and their calculation should not ignore the reality that substitutability between products is generally a matter of degree. To this end a 'weighted market share' approach is discussed.